Abrasion‐resistance of UHMWPE reinforced by illite‐smectite interstratified clay and low dose radiation. Issue 2 (26th November 2021) - Zhang, Xiaodong; Dong, Penggang; Cheng, Guojun; Zhao, Bo; Tang, Zhongfeng
Abstract: Ultra‐high molecular weight polyethylene (UHMWPE)/illite‐smectite interstratified clay minerals (ISIC) composites were irradiated by γ‐ray in air and N2 at 75 kGy. The abrasion‐resistance of composites were studied via a ring‐on‐ring friction tester under dry friction conditions. Compared with virgin UHMWPE, the friction coefficient and wear rate of UHMWPE filled with 0.5 wt% ISIC powders and irradiated by γ‐ray in N2 could be further reduced by near 3.1% and 88.0%, respectively. The worn surfaces of the UHMWPE/ISIC composites irradiated in N2 were relatively smooth after dry friction. The composites exhibited relatively high wear resistance. ISIC powders can play the role of heterogeneous nucleation and induce the crystallization of UHMWPE, thereby improving the abrasion‐resistance. The linear molecular chain of UHMWPE was transformed into a three‐dimensional crosslinked structure after irradiation, which can effectively enhance the plastic deformation resistance and then improve the tribological properties. The results show that low filling amount of ISIC powders and γ‐ray irradiation in N2 are effective strategies to improve abrasion resistance of UHMWPE.